Grafitos sobre cerámica y marcas sobre piedra en el oppidum celtíbero-romano de los Rodiles (Guadalajara) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The findings of several graffiti on pottery as well as some traces on stones in the oppidum of Los Rodiles increase the corpus of the Celtiberian lenguage, based on stratigraphic and chronolological probed supports.
Keywords: : Gaffiti on Pottery; Celtiberian Language; Indigenous Societies; Roman Conquest